Accumulation of quaternary ammonium compounds as emerging contaminants in sediments collected from the Pearl River Estuary, China and Tokyo Bay, Japan. (November 2018) - Dai, Xi; Wang, Cuicui; Lam, James C.W.; Yamashita, Nobuyoshi; Yamazaki, Eriko; Horii, Yuichi; Chen, Weifang; Li, Xiaolin
Abstract: In this work, the distribution of quaternary ammonium compounds (QACs) in two dated sediment cores, collected from the Pearl River Estuary (PRE) and Tokyo Bay (TB), were investigated to understand the historical input of QACs and their diagenetic behavior in urban estuarine environments. The vertical variation profiles of QAC concentrations showed that benzylalkyldimethyl ammonium compounds (BACs) and dialkyldimethyl ammonium compounds (DADMACs) were widely used during 1970s and 1980s both in China and Japan. The declining environmental concentrations of QACs suggested a compositional change of commodities and the effectiveness of emission control strategies. For the individual QAC homologues, BAC homologues decreased significantly over time, while DADMAC compositions remained relatively stable. The differences in concentration and composition profiles of BACs and DADMACs in the sediment cores provided useful information on the patterns of use of QACs in China and Japan, as well as their diagenetic behaviors in the sediments. Graphical abstract: Highlights: Historical occurrence of quaternary ammonium compounds (QAC) was reported in Asia. Usage pattern of QAC is extrapolated in the dated sediment cores. Diagenetic behaviors of QAC were presented in the sediments.